Progressive Collapse Assessment for Concrete Multi-Story Buildings – Review (Eurasian Journal of Engineering and Technology, 2022)
Progressive collapse is a catastrophic partial or complete failure of a structure that occurs when a primary structural component or more, such as a column or any vertical load-bearing component, is lost or damaged. This loss maybe caused by a car accident, an airplane crash, a service system explosion, a missile used in a military operation, a bomb used in a crime or building destruction, a hurricane, a tornado, or an earthquake, as well as other natural disasters. Because of the numerous collapses that have happened since the turn of the century, the progressive collapse has become a popular research topic. Therefore, numerous international structural codes and standards have begun to pay attention to the resistance of facilities to progressive collapse and have formulated guidelines to limit this phenomenon